2013
DOI: 10.1016/j.ydbio.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The N-BAR domain protein, Bin3, regulates Rac1- and Cdc42-dependent processes in myogenesis

Abstract: Actin dynamics are necessary at multiple steps in the formation of multinucleated muscle cells. BAR domain proteins can regulate actin dynamics in several cell types, but have been little studied in skeletal muscle. Here, we identify novel functions for the N-BAR domain protein, Bridging integrator 3 (Bin3), during myogenesis in mice. Bin3 plays an important role in regulating myofiber size in vitro and in vivo. During early myogenesis, Bin3 promotes migration of differentiated muscle cells, where it colocaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 56 publications
(102 reference statements)
0
27
0
Order By: Relevance
“…Other classes of BAR domain containing proteins may also be important for promoting GRAF-independent muscle fusion. For example, two members of the Bridging integrator (Bin) family, Bin1 and Bin3 have been shown to regulate differentiation and fusion of skeletal myoblasts (Fernando et al, 2009; Simionescu-Bankston et al, 2013; Wechsler-Reya et al, 1998). Interestingly, while Bin3 is an N-BAR only containing protein, recent studies indicate that it, like GRAF1, also regulates actin dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other classes of BAR domain containing proteins may also be important for promoting GRAF-independent muscle fusion. For example, two members of the Bridging integrator (Bin) family, Bin1 and Bin3 have been shown to regulate differentiation and fusion of skeletal myoblasts (Fernando et al, 2009; Simionescu-Bankston et al, 2013; Wechsler-Reya et al, 1998). Interestingly, while Bin3 is an N-BAR only containing protein, recent studies indicate that it, like GRAF1, also regulates actin dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while Bin3 is an N-BAR only containing protein, recent studies indicate that it, like GRAF1, also regulates actin dynamics. Simionescu-Bankston et al recently showed that Bin3 associates with and promotes the activation of the Rho-related GTPases Cdc42 and Rac1 in myoblasts (Simionescu-Bankston et al, 2013). Notably, activation of these GTPases is often associated with an inhibition of RhoA; however the effect of Bin3 on RhoA activity was not directly tested in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence also indicates a critical function for branched actin polymerization during Drosophila indirect flight muscle fusion (4). The essential role of the cytoskeleton in fusion is conserved in mammals, in which the actin regulators Rac1, cdc42, and N-WASp are required for muscle development (5)(6)(7)(8). In addition to actin dynamics, numerous proteins that regulate diverse cellular processes have been associated with myoblast fusion (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Cultures were Ͼ95% myogenic as defined by MyoD immunostaining. Cells were cultured in growth media and switched to differentiation media (DM) for 24 or 40 -48 h as previously described (66). Experiments involving animals were performed in accordance with approved guidelines and ethical approval from Emory University's Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…N-BAR domain proteins, such as Bin3, link membrane dynamics to the actin cytoskeleton (21,57). In addition, we showed that Bin3 is important for lamellipodia formation and muscle cell motility, as well as myotube formation and growth (66). Small heat shock proteins, such as Hsbp3, inhibit actin polymerization by acting as capping proteins or may protect the actin cytoskeleton against disruption induced by various stressful conditions (42).…”
Section: Ckb Is Localized In Both Myocytes and Myotubesmentioning
confidence: 95%